Beginning C# and .NET - Benjamin Perkins, Jon D. Reid (Wiley, 2021)
Get a running starttolearning C#programmingwith this fun and easy-to-readguide Asone of the most versatile and powerful programming languagesaround, you might thinkC# would be an intimidating language to learn. Itdoesn'thave to be! In Beginning C# and.NET: 2021 Edition, expert Microsoft programmer and engineer Benjamin Perkinsand program manager Jon D. Reidwalk youthroughthe precise, step-by-step directionsyou'llneed to follow to becomefluent in the C# language and.NET. Using the proven WROX method, you'lldiscover howto understand and write simple expressions and functions, debug programs, work with classes and class members, work with Windows forms, program for the web, and access data.You'lleven learn about some of the new features included in the latest releases of C# and.NET, including data consumption, code simplification, and performance. The book also offers: * Detailed discussions of programming basics, like variables, flow control, andobject-orientedprogramming that assume no previous programmingexperience * "Try it Out" sections to help you write useful programming code using the steps you've learned in thebook * Downloadable code examples from wrox.com Perfect for beginning-level programmers who are completely new to C#, BeginningC#and.NET: 2021 Edition is a must-have resource for anyone interested in learning programming and looking for afun andintuitive place to start.